Development and analysis of mathematical models for photovoltaic converters of solar batteries for avionics systems - Meniailo, O.D.; Grigorieva, O.V.; Makhonin, V.G. (Radiotekhnika, 2025)
The paper considers methods for applying mathematical models of photoconverter parameters to the design and development of technical equipment for receiving, converting and storing solar energy. Considerable attention is paid to determining the optimal power point, and therefore the optimal operating mode of the photovoltaic converter, which, in turn, requires knowledge of its volt-ampere characteristics. For this purpose, the characteristics of the converters were simulated using both certain empirical data and analytical relationships obtained using the equivalent circuit of the photoelectric converter. The paper presents both theoretical relationships of the photoelectric converters parameters and the results of experimental studies of the characteristics dependence on temperature and illumination level. The high correspondence of the mathematical models to the experimental data was confirmed. The developed models demonstrated their adequacy to temperatures of the order of –50 °C. Ways of possible extrapolation of the characteristics to even lower temperatures are shown. In this case, it is recommended to use special measures, the simplest of which may be, for example, the use of a special linear or fragmentary-linear function.